INTERPRETASI SABAR DALAM AL-QUR’AN: Studi Komparatif Al-Qurthubi dan Ibnu Katsir - Zabidi, Ahmad; Hamnah, Hamnah; Maulana, Maulana (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
When someone experiences adversity or a test from Allah Swt., they frequently use the expression